Planejamento turístico regional: um estudo da região Costa Oeste do Paraná. - Ribeiro, Angela Mara Bento (2005)
The present study aims to analyze the west cost region of Paraná State from a touristy perspective, specially by the regional tourist planning, considering the programmes, plans and projects managed by federal, state, regional and county public policies. This area started with the Itaipu Binacional Hydroeletric Plant and its lake, constituting a new tourist landscape in that region. Inicially, there were eight counties, and nowadays fiftheen are settled in the region. All these counties, named "lindeiros" or (neighbours) to the Itaipu Lake, look for their development through integrated tourist actions. Starting from the regional and then to the local space, we also investigate Itaipulândia county that is a representative of this region because of the investment in tourist equipments, its history, and resources accrue from Itaipu.